KINERJA USAHA PEDAGANG TANAMAN HIAS DI KECAMATAN DENPASAR TIMUR KOTA DENPASAR: KINERJA USAHA PEDAGANG TANAMAN HIAS DI KECAMATAN DENPASAR TIMUR KOTA DENPASAR - Krismayana, Ida Bagus Putu Angga; Putra, I Gede Setiawan Adi (Universitas Duta Bangsa Surakarta, 2025)
Entrepreneurial characteristics have an important role in improving business performance, especially for business actors. These characteristics are able to show that entrepreneurship is a practical thing to overcome problems that exist in the business. The purpose of this study is to analyze the relationship between entrepreneurial marketing, entrepreneurial leadership, and entrepreneurial self-efficacy, and business performance through the entrepreneurial competence of ornamental plant traders in East Denpasar District, Denpasar City. The sample in this study was taken using the probability sampling method, namely simple random sampling with a total of 68 respondents. The research data was obtained from the results of the survey, namely structured interviews using questionnaire tools and in-depth interviews by providing a list of questions to complement the data obtained from the results of structured interviews. This study was analyzed using descriptive statistical analysis methods and inferential statistics with SmartPLS 4 software. The results of the study show that entrepreneurial characteristics consisting of entrepreneurial marketing, entrepreneurial leadership, and entrepreneurial self-efficacy are significantly related to business performance through entrepreneurial competence in ornamental plant traders in East Denpasar District, Denpasar City. Traders are expected to be able to continue the implementation of these three entrepreneurial characteristics, namely by marketing innovative ornamental plants, organizing business runs in a structured and sustainable manner, and improving experience in the field of ornamental plants through workshop activities.